Hypoxanthine-guanine phosphoribosyltransferase. Characterization of a mutant in a patient with gout. - Fox, I H (1975)
The mutation in a young gouty male with a partial deficiency of hypoxanthine-guanine phosphoribosyltransferase has been evaluated. The serum uric acid was 11.8 mg/100 ml, and the urinary uric acid excretion was 1,279 mg/24 h. Erythrocyte hypoxanthine-guanine phosphoribosyltransferase was 34.2 nmol/h/mg, adenine phosphoribosyltransferase was 36.5 nmol/h/mg and phosphoribosylpyrophosphate was 2.6 muM. Hypoxanthine-guanine phosphoribosyltransferase from peripheral leukocytes and cultured diploid skin fibroblasts was within the normal range, but enzyme activity in rectal mucosa was below the normal range. Initial velocity studies of the normal enzyme and the mutant enzyme from erythrocytes with the substrates hypoxanthine, guanine, or phosphoribosylpyrophosphate showed that the Michaelis constants were similar. Product inhibition studies distinguished the mutant enzyme from the normal enzyme. Hyperbolic kinetics with increasing phosphoribosylpyrophosphate were converted to sigmoid kinetics by 0.2 mM GMP with the mutant enzyme but not with the normal enzyme. The mutant erythrocyte hypoxanthine-guanine phosphoribosyltransferase was inactivated normally at 80 degrees C and had a normal half-life in the peripheral circulation. The mol wt of 48,000 was similar to the normal enzyme mol wt of 47,000. With isoelectric focusing, the mutant erythrocyte enzyme had two major peaks with isoelectric pH's of 5.50 and 5.70, in contrast to the isoelectric pH's of 5.76, 5.82, and 6.02 of the normal isozymes. Isoelectric focusing of leukocyte extracts from the patient revealed the presence of the mutant enzyme. Cultured diploid fibroblasts from the propositus appeared to function normally, as shown by the inability to grow in 50-100 muM azaguanine and by the normal incorporation of [14C]hypoxanthine into nucleic acid. In contrast, erythrocytes from the patient displayed abnormal properties, including the increased synthesis of phosphoribosylphyrophosphate and elevated functional activity of orotate phosphoribosyltransferase and orotidylic decarboxylase. These unique kinetic, physical, and functional properties provide support for heterogeneous structural gene mutations in partial deficiencies of hypoxanthine-guanine phosphoribosyltransferase.